2020
DOI: 10.1038/s41598-020-66012-x
|View full text |Cite
|
Sign up to set email alerts
|

A treponemal genome from an historic plague victim supports a recent emergence of yaws and its presence in 15th century Europe

Abstract: Developments in techniques for identification of pathogen DNA in archaeological samples can expand our resolution of disease detection. Our application of a non-targeted molecular screening tool for the parallel detection of pathogens in historical plague victims from post-medieval Lithuania revealed the presence of more than one active disease in one individual. In addition to Yersinia pestis, we detected and genomically characterized a septic infection of Treponema pallidum pertenue, a subtype of the trepone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 70 publications
(60 reference statements)
3
31
0
Order By: Relevance
“…Historically, syphilis is commonly believed to have caused a large epidemic across Renaissance Europe, having previously been absent or unrecognized 1,2 . Although the origins of syphilis and the accurate dating of the most recent common ancestor of TPA are still the subject of debate [3][4][5][6] , it is suggested that the strains of TPA that persist in human populations today can be traced back to its introduction into Western Europe approximately 500 years ago, and its subsequent dissemination globally 3,4,6 .Following the introduction of effective antibiotics after World War II, syphilis incidence fluctuated 7 without disappearing, until the 1980s and 1990s during the HIV/AIDS crisis when disease incidence declined markedly 8 , linked to community-wide changes in sexual behaviour, shifting of affected populations, AIDS-related mortality and widespread antimicrobial prophylaxis of HIV-infected populations. However, since the beginning of the twenty-first century, there has been a substantial resurgence in syphilis incidence 9-14 .…”
mentioning
confidence: 99%
“…Historically, syphilis is commonly believed to have caused a large epidemic across Renaissance Europe, having previously been absent or unrecognized 1,2 . Although the origins of syphilis and the accurate dating of the most recent common ancestor of TPA are still the subject of debate [3][4][5][6] , it is suggested that the strains of TPA that persist in human populations today can be traced back to its introduction into Western Europe approximately 500 years ago, and its subsequent dissemination globally 3,4,6 .Following the introduction of effective antibiotics after World War II, syphilis incidence fluctuated 7 without disappearing, until the 1980s and 1990s during the HIV/AIDS crisis when disease incidence declined markedly 8 , linked to community-wide changes in sexual behaviour, shifting of affected populations, AIDS-related mortality and widespread antimicrobial prophylaxis of HIV-infected populations. However, since the beginning of the twenty-first century, there has been a substantial resurgence in syphilis incidence 9-14 .…”
mentioning
confidence: 99%
“…The causes of differential mortality within populations had previously received little more than rudimentary attention in most histories of pre-modern disease. Ancient DNA provided a new perspective, by showing endemic infectious diseases increased the risk of dying during times of major epidemics such as the Black Death [ 16 , 17 ]. For instance, Salmonella enterica contributed to catastrophic population collapse in Mesoamerica during the 16 th century European conquest, but also was part of the background disease landscape in 13 th century Norway [ 11 , 18 , 19 ].…”
Section: Main Textmentioning
confidence: 99%
“…Treponema pallidum pallidum and pertenue (causative agents of syphilis and yaws, respectively) sit at the other end of the spectrum because they lack an outer cell membrane altogether. This feature, coupled with the low pathogenic load of Treponema in late stages of infection [ 45 ], largely precluded its identification in ancient remains [ 45 , 46 , 47 ] until the recent application of high-throughput sequencing methods [ 15 , 17 , 48 ].…”
Section: Main Textmentioning
confidence: 99%
“…Trauma, tuberculosis, treponematosis, metabolic disorders and endocrine disturbances, skeletal dysplasias, tumors, dental diseases and other topics were studied, while numerous publications received international interest (Jankauskas and Gerhards, 2012). Collaboration with foreign colleagues is essential in this field, therefore the osteological collection was successfully included in the international Global History of Health project (Steckel and Rose, 2002), and was examined for research with the Anthropology Department of the University of Central Florida (Holder et al, 2017;Piličiauskas et al, 2017;Whitmore et al, 2017) and the Max Planck Institute (Giffin et al, 2020). This clearly proves that the human osteological collection in Vilnius University can provide significant data related to certain disease development in the past, or reveal some topics that are still not equally covered in some regions or time periods.…”
Section: -Presentmentioning
confidence: 99%